Estado Moderno e garantias individuais: abordagem antropológica sobre a regulamentação da cannabis medicinal - Campos, José Tiago de Queiroz Mendes (2022)
This research on the relationship of the Brazilian state with the regulation of marijuana for scientific and medicinal purposes starts from the recomposition of a broad historical scenario of the development of the Brazilian state and falls on the current management of public policies on drugs in various ways of institutionalization. The activation of these avenues was monitored through collectives that defend an anti-prohibitionist approach to drugs, such as the Marijuana March of Fortaleza, Renfa/CE, Rede Reforma and PBPD, as well as associations of patients who use Cannabis to medicinal purposes, observing, from there, the forms of incidence of these actors in technical, legal and political bodies of the Brazilian state. The understanding of the prohibition process started in the last century: starting with the indication of a public health problem turned into a public safety problem in the name of controlling illegally registered substances, but whose toxicity or addictive potential do not obey a guided scientific classification predominantly in the empirical field, being loaded with moral values attributed to the consumption of certain substances, among which Cannabis spp. both for its wide dissemination in the social environment, and for its unusual claim (to the prohibitionist project), of granting habeas corpus to ensure the freedom of those who resort to the cultivation of this plant with the purpose of protecting their own health through the use of marijuana as a therapeutic tool that increases the patient's quality of life. For the articulation of these different approaches that claim to expand the possibilities of carrying out research that scientifically clarify the risks and benefits involved in treatment with cannabinoids, which aim to overcome the obstacles or institutional gaps that, on this topic, impact the sphere of the fundamental rights of Brazilian citizenship and have repercussions on the social challenges that the regulation of marijuana, even for scientific or medicinal purposes, raises, resorting to the analytical category “mode of existence” (LATOUR, 2012). Emphasizing the referential, legal, political and moral modes of existence, as well as their intersections and overlaps of some of the decision-making processes carried out by the different agents of public agencies of the Brazilian state who manifested themselves in relation to Cannabis spp. for scientific and medicinal purposes.